2015
DOI: 10.1016/j.amjsurg.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Idle time: an underdeveloped performance metric for assessing surgical skill

Abstract: Background The study aim was to evaluate validity evidence using idle time as a performance measure in open surgical skills assessment. Methods This pilot study tested psychomotor planning skills of surgical attendings (N=6), residents (N=4) and medical students (N=5) during suturing tasks of varying difficulty. Performance data were collected with a motion tracking system. Participants’ hand movements were analyzed for idle time, total operative time and path length. We hypothesized that there will be short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 25 publications
(23 reference statements)
0
40
0
Order By: Relevance
“…The main limitations for subjectivebased methods rise in their off-line nature or the response biases related to personal and motivational factors [15]. Computer-based methods have very limited applicability outside expensive simulation laboratories [16,17]. Thus, the development of objective and feasible systems to assess surgical task load remains a major challenge in the healthcare field [18,19].…”
mentioning
confidence: 99%
“…The main limitations for subjectivebased methods rise in their off-line nature or the response biases related to personal and motivational factors [15]. Computer-based methods have very limited applicability outside expensive simulation laboratories [16,17]. Thus, the development of objective and feasible systems to assess surgical task load remains a major challenge in the healthcare field [18,19].…”
mentioning
confidence: 99%
“…In review of the literature, we identified recent work that similarly demonstrated varying kinematics when participants performed interrupted suture tasks on a variable tissue simulator. Specifically, on a model simulating friable tissue, participants had significantly increased idle time, 22 suture time, and path length 23 compared to arterial or fascial tissue models.…”
Section: Methodsmentioning
confidence: 99%
“…This technology can be highly useful in differentiating individual fingers in the recording of suturing skills where markers operate in close proximity to each other. 18 In addition, the IREDs are much brighter than a reflective marker and can be operated at much higher sampling frequencies and with greater accuracy than a passive system.…”
Section: Active Infraredmentioning
confidence: 99%
“…Performance in each of these measures is highly procedure specific, but the data provide useful predictors of skill, as they are shown to differ between novices and experts 12,17 as well as with task difficulty. 18 Motion capture technology spans a variety of methodologies and types of electronic sensors. Those most commonly used in the study of human performance of complex manual skills include (1) optical tracking, (2) accelerometry-based tracking, and (3) magnetic tracking.…”
Section: Motionmentioning
confidence: 99%